Human Resources and Performance of Deposit-Taking Savings and Credit Cooperative Societies in Kirinyaga County, Kenya - Nancy Waithira Murage; Paul Waithaka (European Scientific Journal, ESJ, 2025)
Deposit-taking savings and credit cooperative societies (SACCOs) in Kirinyaga County face several challenges, including low profitability, high retrenchment rates, and slow adoption of new technologies, which hinder their financial stability and operational efficiency. This study investigates how human resources affect SACCO performance while drawing on resource-based theory. A descriptive research design was employed, utilizing both qualitative and quantitative data collection methods. Semi-structured questionnaires were administered to SACCO managers and employees, while secondary data was sourced from financial reports. A sample of ten SACCOs in Kirinyaga County was analyzed using statistical techniques to assess the relationship between organizational resources and performance. The findings reveal that whereas human capital, particularly well-trained staff, is the most significant factor in enhancing SACCO performance, its impact is comparatively lower. The study concludes that strategic investment in human capital is essential for improving SACCO performance. It recommends prioritizing staff training and development to maintain competitiveness. These insights provide a roadmap for SACCOs to enhance efficiency, sustain growth, and improve their role in economic development.